Pelestarian Khazanah Terbitan Daerah Melalui Layanan Deposit: Implementasi Undang-Undang Nomor 13 tahun 2018 - Islamiati, Alda Amalia Nur; Haqqi, Athiatul (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2021)
Introduction. This article discusses the role of the Jambi Provincial Library and Archives Service (DPAD) in preserving regional publications through deposit services. The purpose of this study was to find out the implementation of Law Number 13 of 2018 on the Jambi Province Regional Deposit Collection at the Jambi Province DPAD, to find out the obstacles faced by the Jambi Province DPAD deposit service in implementing Law Number 13 of 2018 concerning the Handover of Printed and Printed Works. Recording work. Research methods. This research uses descriptive qualitative method. Collecting data using observation, interview, and documentation techniques. Data analysis. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. Then the data triangulation technique was carried out. Results and Discussion. The results of this study indicate that the implementation of Law Number 13 of 2018 carried out by the Jambi Province DPAD Deposit Service is socializing, sending letters, carrying out hunting activities and providing lending services and reading services on the spot and giving warning letters to publishers who do not implement the Act. Law Number 13 of 2018. The obstacles faced are the lack of awareness of the publishers and the absence of strict sanctions against publishers, the library is less aware of the existence of private public publishers in the area. Conclusions and suggestions. The implementation of Law Number 13 of 2018 in the Jambi Province DPAD has been implemented but has not been effective. It is better to have more routine socialization regarding the contents of Law Number 13 of 2018.